A randomized controlled trial to verify the irrigation of salivary glands in relieving xerostomia in patients with Sjögren’s syndrome - Du, Hongming; Fu, Zhen; Zhong, Yi; Yuan, Yi; Zhao, Jing; Ding, Xu; Li, Sheng; Gao, Shiyu; Zhu, Yuchi; Song, Haiyang; Wu, Heming (Frontiers in Immunology, 2022)
Objective: To verify the effect of triamcinolone acetonide (TA) and major salivary glands saline irrigation on relieving xerostomia in Sjögren's syndrome (SS) patients. Methods: The enrolled 42 SS patients were randomly assigned to control group (no irrigation), saline group (irrigation with saline) and TA group (irrigation with TA). Each group of 14 cases was treated differently and received the same examinations. The examinations include unstimulated whole saliva flow (UWS), chewing-stimulated whole saliva flow (SWS), citric acid-stimulated parotid flow (SPF), Clinical Oral Dryness Score (CODS), Xerostomia Inventory (XI) and EULAR SS Patient Reported Index (ESSPRI) of 1 week before irrigation (T0) and 1 week (T1), 8 weeks (T8), 16 weeks (T16) and 24 weeks (T24) after major salivary irrigation. Results: Both TA and saline irrigation of major salivary glands resulted in higher SWS and SPF of T8, T16 and T24 than those at T0. ESSPRI (oral dryness domain) of T8, T16 and T24 were significantly lower than that at T0 (P < 0.05). The SWS and SPF of T8, T16 and T24 in the saline group were significantly higher than those in the control group (P< 0.05). XI and ESSPRI (oral dress domain) of T8, T16 and T24 in the saline group were significantly lower than those in the control group (P< 0.05). The SWS and SPF of T16 and T24 in the TA group were significantly higher than those in the control group (P< 0.05). All follow-up cases in the three groups were divided into responders and non-responders. Compared with responders, the UWS, SWS, SPF and CODS of T0 in non-responders were significantly increased (P<0.05). Compared with responders, the XI and ESSPRI of T0 in non-responders were significantly decreased(P<0.05). Conclusion: Irrigation of major salivary glands by TA and saline relief xerostomia in SS patients. Patients with non-severe xerostomia (responders) had better relief after irrigation than patients with severe xerostomia (non-responders). Clinical trial registration: www.chictr.org.cn, identifier ChiCTR210052314.